Heat, Moisture and Air Transfer Properties of Selected Woven Fabrics in Wet State (Journal of Fiber Bioengineering and Informatics, 2009)
The most important parameters characterizing thermophysiological comfort of sport and protective garments are thermal resistance, water vapour permeability and air permeability. Contrary to common textiles, protective and functional garments and some technical textiles like textile dressings are also used in wet state, which affects their comfort properties. However, common measuring instruments mostly do not enable reliable measurement of wet fabrics, due to long time of measurement, during which the fabrics get dry. In this paper two fast measuring PC evaluated instruments ALAMBETA and PERMETEST commercial instruments are described, which provide reliable non-destructive measurement of thermal conductivity, thermal resistance and water vapour permeability of fabrics in dry and wet state. By means of these instruments, thermal resistance and water vapour permeability of heavy cotton and cotton/PES woven fabrics in wet state were experimentally determined and results were discussed. The effect of structure and composition on the above-mentioned properties of these fabrics has been investigated as well. Some surprising results were achieved: with increasing fabrics humidity, the air permeability almost linearly decreased, whereas the total cooling heat flow (due to water evaporation from the wet fabric surface) slowly increased.
Keywords: Clothing comfort; thermal resistance; water vapour permeability; wet textile fabrics